PENEMUAN RUTE TERPENDEK PADA APLIKASI BERBASIS PETA - Wira Buana, Putu (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 1, No. 1 Desember 2010)
Graphical Information System (GIS) is a widely used network modeling of real world into the base map. Some of the issues modelled are highway network traffic, irrigation networks and power grids ranging from substations to customers. The final results of this study will be used to search the shortest route for variety public purposes that are currently faced with the difficulties of transportation such as highway congestion. The test results by using some different routes and comparison calculations have shown the right route compared with the conditions in the field.
Keywords: GIS, maps, shortest route, highway